RESPON SISWA TERHADAP MODEL EXPERIENTIAL LEARNING DALAM PEMBELAJARAN MENULIS TEKS INSPIRATIF DI SMP - Yeni Safitri; Ika Mustika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is based on the low ability to write inspirational texts of students in junior high school. Thus, researchers offer a model of experiential learning as an alternative to teaching and learning so that learning can be more meaningful. In this case, the formulation of the problem taken in the research is how students respond to the use of experiential learning models? The study aims to determine students' responses to the experiential learning model. The method used is descriptive qualitative. From the data processing method in this study, the results of 9% of students' positive responses to the use of experiential lerning models were obtained.